2014
DOI: 10.1186/s13000-014-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between cyclin D1 G870A polymorphism and cervical cancer risk: a cumulative meta-analysis involving 2,864 patients and 3,898 controls

Abstract: BackgroundAssociation between Cyclin D1 (CCND1) polymorphism and cervical cancer risk are conflicting with published articles. We performed a meta-analysis to investigate the association between CCND1 G870A polymorphism and cervical cancer risk.MethodsPubMed, Embase and CNKI data were researched to conduct a meta-analysis on the associations between CCND1 G870A polymorphism and cervical cancer risk. Ten published case–control studies including 2,864 patients with cervical cancer and 3,898 controls were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In another study, no significant association was reported between the CCND1 SNP (rs9344) and overall risk for cervical cancer in the Asian population but on stratification analysis by race, individuals carrying the AA or AA/AG genotypes showed a significant higher risk in comparison with GG carriers [ 32 ]. In parallel to the findings from the present study, Hu et al (2014) [ 30 ], also did not find the association of CCND1 G870A polymorphism and cervical cancer risk amongst different ethnic groups including Asian, Caucasian, and mixed in a cumulative meta-analysis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In another study, no significant association was reported between the CCND1 SNP (rs9344) and overall risk for cervical cancer in the Asian population but on stratification analysis by race, individuals carrying the AA or AA/AG genotypes showed a significant higher risk in comparison with GG carriers [ 32 ]. In parallel to the findings from the present study, Hu et al (2014) [ 30 ], also did not find the association of CCND1 G870A polymorphism and cervical cancer risk amongst different ethnic groups including Asian, Caucasian, and mixed in a cumulative meta-analysis.…”
Section: Discussionsupporting
confidence: 89%
“…However, these reports are conflicting thus we performed meta-analysis on the literature available in order to provide more accurate information on the role of CCND1 G870A (rs9344) polymorphism and overall cancer risk in Indian population. Although, various meta-analyses on individual cancer susceptibility have been published globally [ 30–35 ]. Pabalan et al (2008) [ 51 ], performed a meta-analysis on role of CCND1 polymorphism in different types of cancers and populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one SNPs (rs9344) have been reported to have clinical significance. rs9344 is a synonymous SNP and has been associated as a risk factor SNP for different types of cancer [20][21][22][23][24][25] in different population including breast cancer [22,26]. In Chinese population, this SNP did not show to have a major association with breast cancer.…”
Section: Utr Snp Effect On Cyclin D1mentioning
confidence: 99%